2022
DOI: 10.1364/oe.455312
|View full text |Cite
|
Sign up to set email alerts
|

2.805 Gbit/s high-bandwidth phosphor white light visible light communication utilizing an InGaN/GaN semipolar blue micro-LED

Abstract: We propose and implement a high-bandwidth white-light visible light communication (VLC) system accomplishing data rate of 2.805 Gbit/s utilizing a semipolar blue micro-LED. The system uses an InGaN/GaN semipolar (20-21) blue micro-LED to excite yellow phosphor film for high-speed VLC. The packaged 30 μm 2 × 4 blue micro-LED array has an electrical-to-optical (EO) bandwidth of 1042.5 MHz and a peak wavelength of 447 nm. The EO bandwidth of the white-light VLC system is 849 MHz. Bit error rate (BER) of 2.709 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Thus, blue μLEDs exhibit the highest reported modulation bandwidth among all wavelength devices. Currently, c-plane μLEDs have a lower bandwidth than nonpolar or semipolar μLEDs; however, bandwidths greater than 1 GHz can be achieved by structural optimization or growth of microstructures 86,90,95,96 . In addition, the use of QDs as active regions also helps reduce the carrier lifetime of the device 91,93 .…”
Section: Approaches To Increasing the Modulation Bandwidthmentioning
confidence: 99%
“…Thus, blue μLEDs exhibit the highest reported modulation bandwidth among all wavelength devices. Currently, c-plane μLEDs have a lower bandwidth than nonpolar or semipolar μLEDs; however, bandwidths greater than 1 GHz can be achieved by structural optimization or growth of microstructures 86,90,95,96 . In addition, the use of QDs as active regions also helps reduce the carrier lifetime of the device 91,93 .…”
Section: Approaches To Increasing the Modulation Bandwidthmentioning
confidence: 99%
“…1 Recent studies have shown that the new VLC system built by the new VLC light sources laser diodes (LDs) and micro-light emitting diode (micro-LEDs) has achieved a huge breakthrough in communication rates compared to LED, which are both reaching Gbps. 2,3 However, for LDs and micro-LEDs light sources, LED light sources have the advantages of longer communication distances, nonstrict alignment, simple production processes, driver circuits, and low cost, making them widely used in market lighting systems. LED-based VLC systems have the following advantages: 4 (i) combining lighting and communication functions; (ii) resistant to electromagnetic interference; (iii) available unlicensed bandwidth; (iv) less harmful to humans and the environment; and (v) low laying cost.…”
Section: Introductionmentioning
confidence: 99%
“…Visible light communication (VLC) technology is considered a promising complementary technology for wireless communication, which has significant potential for high-speed downlink data transmission in 6G wireless communication systems 1 . Recent studies have shown that the new VLC system built by the new VLC light sources laser diodes (LDs) and micro-light emitting diode (micro-LEDs) has achieved a huge breakthrough in communication rates compared to LED, which are both reaching Gbps 2 , 3 . However, for LDs and micro-LEDs light sources, LED light sources have the advantages of longer communication distances, nonstrict alignment, simple production processes, driver circuits, and low cost, making them widely used in market lighting systems.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development in the field of display technology, the nitride-based μ light-emitting diodes (μLEDs) have been evaluated for wide applications, such as the low-power consume wearable devices [1], wide-viewing angle outdoor displaying and televisions [2,3], high-speed wireless visible light communication [4,5], and high-resolution augmented/virtual reality (AR/VR) products [6]. For high pixels per inch (PPI) display, the size of μLED pixel size needs to shrink to below 20 μm.…”
Section: Introductionmentioning
confidence: 99%